A pendant droplet-based sensor for the detection of acetylcholinesterase and its inhibitors. Issue 71 (13th August 2021) - Li, Benyou; Guo, Yongxian; Jiang, Yifei; Lin, Jin-Ming; Hu, Qiongzheng; Yu, Li
Abstract : Schematic diagram of the pendant droplet-based sensor for the detection of AChE and its inhibitors. Abstract : In this work, a pendant droplet-based sensor is developed for the rapid and label-free detection of acetylcholinesterase (AChE) and its inhibitors. The detection limit of AChE reaches 0.17 mU mL −1 . The pIC50 values of AChE inhibitors such as neostigmine, rivastigmine and galantamine are determined to be 0.45 μM, 0.64 μM and 4.93 μM, respectively.